Desertification: Research Imperatives - Williams, Martin (Annals of Arid Zone, 2016)
This paper elaborates on the need for five major research imperatives relating to desertification. These are (a) disentangling the respective role of human activities and climatic fluctuations as causes of land degradation; (b) clarifying the causes of drought; (c) evaluating possible impacts of future climate change on desertification; (d) assessing ecological attributes and processes within different arid regions; and (e) identifying processes of ‘natural desertification’. Key words: Desertification, land degradation, climate change, drought.